A rare case of subcutaneous traumatic index finger both extensor tendons rupture. Results of WALANT extensor digiti minimi transfer and literature review - Murena, Luigi; Elleni, Alice; De Luca, Alessandro; Canton, Gianluca (Acta Biomedica Atenei Parmensis, 2022)
Traumatic subcutaneous index finger both extensor tendons ruptures are rare injuries. Aim of the present paper is to review the literature about this uncommon lesion and to describe the case of 56 years old woman injured when her hand became stuck under a weight during a wrist hyperflexion movement. Surgical treatment was undertaken after 7 days. An extensor digiti minimi (EDM) tendon transfer and a Pulvertaft tenodesis on the index EDC to middle EDC using wide awake local anesthesia no tourniquet (WALANT) technique was performed. The advantage is to allow immediate visualization of active motion and confirmation of appropriate soft tissue tensioning. In our patient no complications were observed and an early rehabilitation program was started. The patient recovered full function at 2 months and resumed hear heavy labour working activity at 4 months.